2019
DOI: 10.1016/j.healthpol.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

How health policy shapes healthcare sector productivity? Evidence from Italy and UK

Abstract: Does health policy shape healthcare sector productivity? Evidence from Italy and UK. The English (NHS) and the Italian (SSN) healthcare systems share many similar features: basic founding principles, financing, organization, management, and size. Yet the two systems have faced diverging policy objectives since 2000, which may have affected differently healthcare sector productivity in the two countries. In order to understand how different healthcare policies shape the productivity of the systems, we assess, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…Rutkowska-Podołowska et al [91] found that policymakers in Europe are focusing on reducing healthcare spending without drastically reducing the scope of public health services. Such regularities also appeared in other studies [92][93][94][95]. Based on the authors' analyses, it can be concluded that these activities were ineffective because healthcare expenditure was systematically growing in almost all EU countries.…”
Section: Discussionsupporting
confidence: 56%
“…Rutkowska-Podołowska et al [91] found that policymakers in Europe are focusing on reducing healthcare spending without drastically reducing the scope of public health services. Such regularities also appeared in other studies [92][93][94][95]. Based on the authors' analyses, it can be concluded that these activities were ineffective because healthcare expenditure was systematically growing in almost all EU countries.…”
Section: Discussionsupporting
confidence: 56%
“…Second, we also deal with the fact that, in some Italian regions, region-specific recovery plans, called “ Piani di Rientro ”, have been implemented since 2007 in order to recover from the budget deficit related to health care expenditures. 13 Although part of the literature agrees on the fact that being included in such plans helps to contained costs (Atella et al, 2019 ), the consequences in terms of health outcomes are less clear. 14 A dummy variable is therefore included: 1 if the hospital is located in a region included in the recovery plan ( Recovery Plans ), and 0 otherwise.…”
Section: Datamentioning
confidence: 99%
“…Furthermore, as organisations, both the NHS and SSN were founded based on key principles. These include the provision of health services that are predominantly free at the point of use, access to healthcare based on need, irrespective of socioeconomic background, and universal coverage [21].…”
Section: Application To a Uk Based Health Systemmentioning
confidence: 99%